If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -3(a + -5) = 5 Reorder the terms: 2a + -3(-5 + a) = 5 2a + (-5 * -3 + a * -3) = 5 2a + (15 + -3a) = 5 Reorder the terms: 15 + 2a + -3a = 5 Combine like terms: 2a + -3a = -1a 15 + -1a = 5 Solving 15 + -1a = 5 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -1a = 5 + -15 Combine like terms: 15 + -15 = 0 0 + -1a = 5 + -15 -1a = 5 + -15 Combine like terms: 5 + -15 = -10 -1a = -10 Divide each side by '-1'. a = 10 Simplifying a = 10
| k-(-71)=74 | | c-78=(-10) | | 9x^2=-77+18x | | x^3-10x=-3x^2-24 | | j+4=(-85) | | -87=g-92 | | 2a-3b(a-5)=5 | | w+27=(-64) | | 2/x-22=5/x-2 | | x/7-1=2 | | m-68=-48 | | -5=j+5 | | q-(-9)=73 | | 14c-7d= | | 98=-7z | | 2v-15=25 | | -15=w-62 | | 3x+14=-7+2x | | -4n=(-64) | | 10x^2+81x+8=0 | | h+(-91)=6 | | -8j=88 | | c^2-3c-85=0 | | 10x-11-8x+23=6 | | -9h=-99 | | b-(-12)=15 | | -4u-2(-u-15)=8(2u-9) | | 3=j+-9 | | 17=c-(-7) | | 6n^2+29n+28=0 | | 3Cosx=3 | | 12=-4g |